TRANSFORMATION OF MANAGEMENT SYSTEMS IN THE CONDITIONS OF INNOVATIVE ECONOMY (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines how management systems are changing in the conditions of an innovative economy. The transition from an industrial economy to a knowledge-based economy has significantly influenced organizational structures and managerial approaches. The study focuses on the impact of digitalization, artificial intelligence, global competition, and workforce transformation on modern management systems. The article identifies three main dimensions of management transformation: structural, process-related, and cultural. International experience from the United States, Germany, South Korea, and Singapore is analyzed to determine practical lessons for Uzbekistan. The study concludes that successful management transformation requires flexible organizational models, investment in human capital, and effective institutional reforms.
Keywords: Innovative economy, management transformation, digitalization, organizational culture, adaptive management, human capital, Uzbekistan.